Przekształcenia struktury demograficznej w metropoliach Polski - Musiał-Malago, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The process of European integration, increasing globalization, and economic restructuring generate many changes in different fields. One of these changes is the need for cities to strengthen their positions in the world. The cities play a great role in creating urban space. Metropolitan areas are fundamental elements in the settlement system. In the recent years in the world cities are not only the centres of region but also are included in other, which are called network cities. The city network has gained an increasing role in the generation of economic growth. Growing interdependency among cities implies the advancement of urban network. The article presents the transformations of demographic structure and situation in the labour market of the Polish metropolies such as: Warsaw, Cracow, Lodz, Poznan and Wroclaw. The article is based on statistical data provided by the Central Statistical Office between 2000 and 2003. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 281-287